The pitfalls and promises of Chinese-led special economic zones for African development - Phillips, James (School of Economics, 2025)
This dissertation seeks to critically assess the potential of Chinese-led Special Economic Zones (SEZs) in Africa to achieve development objectives and align with the strategic interests of host countries. The research is informed by the exceptional growth trajectory of China, which has resulted in increased Chinese economic engagement with the global south, including the proliferation of Chinese-led SEZs overseas. To shed light on this phenomenon, this work conducts a case study of the Lekki Free Zone – one of China's flagship overseas SEZs in Africa – analyzing the factors pivotal to successful SEZs and supporting development objectives, as well as China's role as an investor and partner. The research findings reveal a pattern of unmet expectations in the achievement of a multitude of development objectives set forth by the zone developer and host country. Notwithstanding these shortcomings, the zone has seen significant modern infrastructure developments, suggesting potential for future growth. Yet, the study identifies an enduring imbalance. This is evident as the Chinese-led SEZ model in Africa seemingly prioritizes the interests of Chinese investors, at times overshadowing the developmental needs of host countries. Such a trend raises questions about the sustainability and equity of these partnerships. The study further synthesizes the findings to provide recommendations for policymakers, investors, and other stakeholders that seek a relationship of more symmetrical benefit.